Flow and reaction characteristics on catalytic upgrading of biomass pyrolysis vapors in novel cyclone reactors. (15th December 2019) - Zhang, Yuchun; Yi, Weiming; Fu, Peng; Li, Zhihe; Bai, Xueyuan; Tian, Chunyan; Wang, Nana; Li, Yongjun
Abstract: To improve the catalytic upgrading efficiency of biomass pyrolysis vapors and reduce secondary cracking of aimed products in current conventional reactors, a novel cyclone reactor was designed for the gas (biomass pyrolysis vapors)-solid (catalysts) heterogeneous reaction. The contact effect of gas-solid two-phase could be increased in the cyclonic flow field, and the separation between the gas products and catalysts occurs while flowing down due to the centrifugal force in short residence time. The rapid separation reduces secondary cracking effectively. In this study, the catalytic upgrading of pyrolysis vapors in the cyclone reactor were investigated from the aspect of fluid dynamics, residence time distribution and catalytic reaction by CFD simulation combining with the experimental method. The results indicate that in the reaction chamber of the cyclone reactor the concentration gradient of catalysts decreases gradually while flowing down. The cyclonic flow is intensified due to the guided vanes in the middle part of the reactor, and the separation effect is improved remarkably. The effects of outlet structures were investigated based on the residence time distribution and the product selectivity, the structure of Case 2 that has a vertical catalyst outlet and a horizontal gas outlet is better. The residence time of catalysts in Case 2 is 1.0s–2.0s. And the overall mass fraction of the bio-oil is 54%. Highlights: A guide vane cyclone reactor for upgrading of biomass pyrolysis vapors was built. The catalyst concentration, RTD and catalytic pyrolysis process were analyzed. The mean residence time of catalysts in the cyclone reactor was 1.0s–2.0s. The overall mass fraction of the bio-oil vapors is around 54%. In this work the effects of outlet structures were investigated.